Spatiotemporal Changes (1945–2020) in a Grazed Landscape of Northern Greece, in Relation to Socioeconomic Changes - Dimitrios Chouvardas; Maria Karatassiou; Petros Tsioras; Ioannis Tsividis; Stefanos Palaiochorinos (Land, 2022)
The spatiotemporal changes of the grazed Greek landscapes in the last 75 years resemble those evidenced in most parts of the northern Mediterranean region, where woody vegetation encroached on open areas changing landscape structure and diversity. These landscape transitions are deeply influenced by demographic and socioeconomic changes that exacerbate the abandonment of traditional management practices including livestock farming and wood harvesting. The aim of this paper was to examine the spatiotemporal changes regarding land use/land cover (LULC) types in a typical grazed landscape of the Lagadas area in northern Greece in the period 1945–2020 and try to associate them with socioeconomic changes. Special attention was given to grassland evolution. Cartographic material in various forms, such as historic (LULC) data sets in shapefile format (1945, 1960 and 1993), recent land use maps (Corine Land Cover of 2018), and satellite images (Google Earth images from 2017 to 2020) was analyzed with Geographic Information Systems software and landscape metrics. Socioeconomic inventory data and grazing animal numbers were also collected and analyzed from diachronic census reports of Greek authorities. Spatiotemporal changes in the Lagadas landscape showed that grasslands, open shrublands and silvopastoral areas decreased during the examined period in favor of dense shrublands and forests, causing a significant reduction in landscape diversity and heterogeneity. Main demographic and socioeconomic drivers were the decrease of the local population, population aging and a significant reduction of employment in the primary economic sector over time. These changes were coupled with reductions in the number of grazing animals (sheep, goats, and cattle), firewood harvesting and charcoal production and were identified as the main reasons for landscape change. Grasslands have become increasingly fragmented and isolated over the years. Future sustainable livestock husbandry in the area is seriously threatened by the ongoing reduction of grasslands and open shrublands.